Q.MÁTMURATOVTÍŃ «TERBENBES» SHÍǴARMASÍNDA JÚREK KOMPONENTLI FRAZEOLOGIZMLER - Shınnazarova, S.J. (ILIM hám JÁMIYET, 2025)
The article discusses phraseological units with the “heart” component in the Karakalpak language. This article examined nomination units with a somatic component in works of art. The linguistic variants and semantics of phraseological units of somatism with components of “heart” are analyzed.